THE IMPORTANCE AND ADVANTAGES OF AUTOMATION OF THE PROCESS OF VERIFICATION AND CALIBRATION OF MEASURING INSTRUMENTS USING SOFTWARE - Jumayev , Odil; Kholov , Abduaziz; Rakhmatov , Doston (Techscience uz - Topical Issues of Technical Sciences, 2025)
This article considers the issues of automating and optimizing the process of comparison and calibration of measuring instruments, which is a key part of metrological services, using software. It also explains the methods and tools for filtering signals when transmitting data from measuring instruments to a computer. Modern technologies for automating the comparison and calibration process and real examples of their application in industry are also presented.